Investigation on the mass sensitivity of quartz crystal microbalance gas sensor using finite element simulation - Md Ralib, Aliza Aini; Nik Mohd Zamri, Nik Nursyahida; Hazadi, Ahmad Hafiz Faqruddin; Ab Rahim, Rosminazuin; Za’bah, Nor Farahidah; Saidin, Norazlina (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI), 2019)
The increasing global trends in healthcare priorities towards improving the effectiveness of diagnostic procedure by utilizing a non-invasive method which is breath analysis. This will benefit in increasing treatment efficiency and also reducing healthcare costs. Breath is a simple technique where the sample are easily obtained and can be provided immediately. The most popular method that had been used in hospital are urine and blood. Contradict with breath, urine and blood take too much time to analyse the disease and a painful process. The detection technique of breath analysis is done by using electroacoustic wave sensor from piezoelectric substrate. This acoustic wave sensor has been used to detect the changes in the frequency where it will be used to detect the disease. Breath analysis is a technique where it uses an electronic nose (E-nose) as a device. E-nose consist of Quartz Crystal Microbalance (QCM) sensor in order to differentiate odor in human breath. QCM is a sensitive weighing device which have a high efficiency. AT-cut quartz was chosen as the piezoelectric material and aluminum as the electrode. The objective of this paper is to design and simulate a QCM sensor for breath analysis application. Other than that, it also to determine the important key parameters that influence the performance of breath analysis which is sensitivity and resonant frequency. QCM sensor is being simulate by using COMSOL Multiphysics software. This is to evaluate the behavior of QCM sensor in terms of Eigen frequency analysis. The simulated QCM sensor with quartz radius of 166 um resonates at 8.871 MHz. The sensitivity of the sensor is 0.167 MHz/ng after exposed to acetone gas which act as the breath marker for detection of diseases in exhaled breath.Hence, the proposed design can be used as a non-invasive approach for early detection of disease through breath analysis.